Linkage Map of Escherichia coli K-12, Edition 10: The Physical Map - Rudd, Kenneth E. (American Society for Microbiology, 1998)
A physical map, EcoMap10, of the now completely sequenced Escherichia coli chromosome is presented. Calculated genomic positions for the eight restriction enzymes BamHI, HindIII, EcoRI, EcoRV, BglI, KpnI, PstI, and PvuII are depicted. Both sequenced and unsequenced Kohara/Isono miniset clones are aligned to this calculated restriction map. DNA sequence searches identify the precise locations of insertion sequence elements and repetitive extragenic palindrome clusters. EcoGene10, a revised set of genes and functionally uncharacterized open reading frames (ORFs), is also depicted on EcoMap10. The complete set of unnamed ORFs in EcoGene10 are assigned provisional names beginning with the letter “y” by using a systematic nomenclature.